Nematode-Associated Bacteria: Production of Antimicrobial Agent as a Presumptive Nominee for Curing Endodontic Infections Caused by Enterococcus faecalis - Donmez Ozkan, Hicran; Cimen, Harun; Ulug, Derya; Wenski, Sebastian; Yigit Ozer, Senem; Telli, Murat; Aydin, Neriman; Bode, Helge B.; Hazir, Selcuk (Frontiers in Microbiology, 2019)
Xenorhabdus and/or Photorhabdus bacteria produce antibacterial metabolites to protect insect cadavers against food competitors allowing them to survive in nature with their nematode host. The effects of culture supernatant produced by Xenorhabdus and Photorhabdus spp. were investigated against multi-drug resistant dental root canal pathogen Enterococcus faecalis. The efficacy of the cell-free culture supernatants from 7 different supernatants of Xenorhabdus and Photorhabdus species against E. faecalis was assessed with overlay bioassay and serial dilution techniques. Additionally, time-dependent inhibition activity of supernatant was evaluated. To determine the bioactive antibacterial compound in the supernatant, antibacterial activity of wildtype, induced and non-induced fclC promoter exchange mutant of X. cabanillasi were tested. The medicament potential of 10-fold concentrated supernatant of induced fclC promotor exchanged X. cabanillasii was also assessed in dental root canals. Among the 7 different bacterial species, X. cabanillasii produced the strongest antibacterial effects. The data showed that the bioactive antibacterial compound was a fabclavine derived from NRPS/PKS. To mimic endodontic therapy process, artificially infected root canals with E. faecalis were irrigated with EDTA, sodium hypochloride, and sterile distilled water, respectively. Subsequently, the root canals were treated with intracanal medicaments, calcium hydroxide paste, or chlorhexidine gel, or fabclavine rich supernatant. Fabclavine rich supernatant was more effective than chlorhexidine and as effective as calcium hydroxide against E. faecalis in the root canal. There was no significant difference between calcium hydroxide and chlorhexidine treatments. The mean percentage of E. faecalis-free dental root canals after treatment was 63.6, 45.5 and 18.2% for fabclavine, calcium hydroxide and chlorhexidine, respectively. Liquid fabclavine or preferably its paste or gel formulation has a great potential alternative to be used as an intracanal medicament.